Prevalence of overweight and obesity, and associations with socio-demographic and etiological factors - Singh, Adity; Rathoria, Ekansh; Singh, Saurabh Kumar; Rathoria, Richa; Yadav, Suresh Kumar; Bansal, Utkarsh (International Journal of Contemporary Pediatrics, 2024)
Background: Adolescent obesity and overweight (OW) prevalence are rising quickly. The present study was done to assess the prevalence of OW and obesity and its association with demographic and etiological factors. Methods: An observational study including 386 adolescents aged 10-19 years was conducted using a pre-designed questionnaire. Anthropometric measurements of weight (kg) and height (cm) were taken and body mass index (BMI) calculated by weight (kg)/height2(m2). The weight status was classified as underweight (UW) <5th percentile, healthy weight (HW) between the 5th and <85th percentile, OW between >85th and <95th percentile, and obese (OB) equal to or >95th percentile using the CDC percentile ranking for BMI-for-age. Statistical data analysis was done by SPSS software version 20. P<0.05 was considered significant. Results: The mean age of adolescents in early, mid, and late adolescent age groups were 11.52 (1.13), 15.01 (0.82), and 17.72 (0.77) years respectively. The overall mean age of adolescents was 14.19 (2.63) years. The mean weight, height, and BMI of adolescents were 44.84 (11.35) kg, 1.54 (0.12) meters, and 18.91 (3.89) kg/m2 respectively. The prevalence of OW and obesity was 11.7%, and 5.4% respectively. A significant association was found between OW and obesity with upper socioeconomic status (p<0.0001), daily junk food intake (p<0.0001), screen time of more than 2 hours per day (p<0.0001), and no or decreased physical activity (p<0.0001). Conclusions: Adolescent obesity is a prevalent issue that requires early primordial and primary intervention through coordinated policy activities made by policymakers and medical professionals.